2020
DOI: 10.1097/brs.0000000000003705
|View full text |Cite
|
Sign up to set email alerts
|

Braces Designed Using CAD/CAM Combined or Not With Finite Element Modeling Lead to Effective Treatment and Quality of Life After 2 Years

Abstract: MiniThe impact of brace design through CAD/CAM with or without finite element modeling was studied over two years in a randomized controlled trial. Clinical outcomes, 3D correction, compliance and quality of life were satisfactory and equivalent between the computational techniques used, demonstrating the validity of simulation in the design process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…A patient-specific FEM simulation of brace donning and tightening was then performed to compute the simulated 3D correction metrics and the pressures exerted on the skin. The FEM used and its validation have been presented in previously published work, 32,33 and is briefly summarized here. For each case, the torso topography scan and the brace model were aligned on the 3D reconstruction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A patient-specific FEM simulation of brace donning and tightening was then performed to compute the simulated 3D correction metrics and the pressures exerted on the skin. The FEM used and its validation have been presented in previously published work, 32,33 and is briefly summarized here. For each case, the torso topography scan and the brace model were aligned on the 3D reconstruction.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical integration of this FEM was validated in a randomized controlled trial of 120 cases where immediate and 2-year correction was evaluated. [30][31][32] Satisfactory treatment outcomes were achieved (83% of patients stayed <45°over 2 yrs) with lighter and thinner braces covering less torso area.…”
mentioning
confidence: 98%
“…When scoliosis is between 25 and 40 degrees, brace treatment is required [1]. Randomised controlled trials (RCTs) have confirmed bracing effectiveness [2,3], supporting the conclusions of a large number of observational studies [4][5][6]. Brace effects depend on different factors: the deformity's characteristics, brace type, construction and material used, brace wear dosage, patients' reactions to the brace, and correct and consistent brace wear throughout therapy [7,8].…”
Section: Introductionmentioning
confidence: 81%
“…Several studies have demonstrated significant improvement in the results using CAD/CAM braces compared to the traditional approach, adding concrete scientific evidence (level of evidence II) [78][79][80]. However, these studies cannot offer a prior guarantee for better treatment results, as several other factors play a crucial role in brace treatment.…”
Section: Cad/cam and Smart Materialsmentioning
confidence: 99%